Biographies of Stone and Landscape: Lithic Scatters - Clive Jonathon Bond (Internet Archaeology, 2009)
Lithic scatters are complex palimpsests. Cores, waste and tools, when interpreted in their landscape context often appear to constitute multiple episodes of activity. These seasonal and cyclical episodes represent different lengths of duration and/or function. This article deals with assemblages from central Somerset, UK, containing artefacts of flint and others of greenstone and sandstone and argues that discarded/deposited artefacts sometimes served as a resource for cultural memory.